Educação Histórica na prática dos professores: o processo de ensino e aprendizagem a partir dos cursos de formação continuada na SME de Curitiba - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2018)
This present work aims to analyze the practice of the History Teachers of the Municipal Teaching System of Curitiba who were part of the continuing education courses focusing on the development of the Historical Education assumptions (RÜSEN, 2010; LEE, 2001; BARCA, 2003, SCHMIDT, 2009) and the influence that these courses have on the teachers' practices. For the development of the research, a qualitative research perspective was followed (BOUTIN; GOYETTE; LESSARDHÉRBERT, 2012), based on the development of the four research poles, which are: the epistemological pole, the theoretical pole, the morphological pole, and the technical pole. For this purpose, we have gathered the projects of continuing education provided by the Municipal Department of Education (SME) in partnership with the Laboratory of Research in Education (LAPEDUH) of the Federal University of Paraná between 2010 and 2016, mapping the teachers that have been part of these courses in order to group them so they could be interviewed with the objective of presenting their considerations about the Historical Education practice in the school environment from the learning gathered in the courses. The project is justified by the trajectory already covered by the courses taught and also by the approximation of the theoretical assumptions of Historical Education based on the basic curriculum (CURITIBA, 2016). The research has shown that the course offers a space for dialogue and teacher learning that aggregates the practice and research of teachers. It also pointed out the substantial differences in the conception of classroom teaching regarding the use of sources and narrative productions by students, taking History as the reference science that guides the learning process. Difficulties were also identified, such as difficulties in communication by the students, as well as the lack of understanding of the school community at many times.
Keywords: Educação Histórica; cursos de formação; formação de professores; Historical Education; Training courses; teachers training courses; CNPQ::CIENCIAS HUMANAS::HISTORIA